The Effectiveness of Acceptance and Commitment-Based Training on Sense of Coherence and Regret of Spouse Selection in Women - Khabazand, Shakiba (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to investigate the effectiveness of Acceptance and Commitment-based training on sense of coherence and regret of spouse selection among women. This study employed an applied, quasi-experimental design with a pretest–posttest format and a control group. The statistical population included all women aged 25 to 45 years who referred to counseling centers in Sari in 2025. A total of 30 participants were selected using purposive sampling and randomly assigned to an experimental group (n = 15) receiving Acceptance and Commitment-based training and a control group (n = 15). Data collection instruments included the Revised Sense of Coherence Scale (Flensborg, 2006) and the Regret of Spouse Selection Questionnaire (Schwartz et al., 2002). The intervention consisted of nine structured sessions of Acceptance and Commitment-based training, each lasting two hours. Data were analyzed using multivariate analysis of covariance (MANCOVA) in SPSS version 26 after confirming statistical assumptions. The results of MANCOVA indicated a significant effect of group membership on sense of coherence (F = 49.28, p < 0.001, η² = 0.40) and regret of spouse selection (F = 31.57, p < 0.001, η² = 0.53) at the posttest stage after controlling for pretest scores. These findings suggest that Acceptance and Commitment-based training significantly increased sense of coherence and significantly decreased regret of spouse selection in the experimental group compared to the control group. Acceptance and Commitment-based training is an effective psychological intervention for enhancing sense of coherence and reducing regret of spouse selection among women, indicating its potential utility in improving psychological well-being and marital-related cognitive-emotional outcomes.